The Nurse’s Contribution To Effective Burn Care Management (The Review of Diabetic Studies, 2025)
Background: Burn injuries are a major global health challenge causing significant morbidity, disability, and mortality, particularly in low- and middle-income countries. Nurses play a pivotal role across all stages of burn management, providing wound care, infection control, pain management, nutrition, rehabilitation, and psychosocial support within multidisciplinary teams.Methods: An integrative literature review was conducted using PubMed, CINAHL, Scopus, and Google Scholar (2010–2025). Studies focusing on nursing interventions in burn care covering acute, rehabilitative, and psychological aspects were analyzed thematically to identify the scope and impact of nursing roles on patient outcomes.Results: Findings highlight that nurses substantially improve burn outcomes through evidence-based wound management, infection prevention, fluid resuscitation, nutritional and emotional support, and patient education. Advances in simulation-based training, telehealth, and digital wound assessment have enhanced care efficiency. However, challenges such as high workloads, emotional stress, and limited resources particularly in resource-poor settings continue to affect care delivery and nurse well-being.Conclusions: Nurses are indispensable to effective burn care, providing holistic, patient-centered interventions that improve survival, recovery, and quality of life. Strengthening specialized education, promoting professional development, and addressing systemic challenges are essential to optimizing nursing performance. Establishing global standards and expanding nursing-led research will further advance burn care practice and ensure equitable outcomes worldwide.